Sheep farmers’ attitudes to farm inspections and the role of sanctions and rewards as motivation to reduce the prevalence of lameness - Liu, Nicola L.B.H.; Kaler, Jasmeet; Ferguson, Eamonn; O’Kane, Holly; Green, Laura E. (Universities Federation for Animal Welfare, 2018)
The Welfare of Farmed Animals (England) Regulations 2007 make it an offence to allow unnecessary suffering to animals, highlighting that farmers have a duty of care for their animals. Despite this, the current global mean prevalence of lameness in sheep in England is 5%; i.e. ~750,000 lame adult sheep at any time. To investigate farmers’ attitudes to sanctions and rewards as drivers to reduce the prevalence of lameness in sheep, farmers’ attitudes to external inspections, acceptable prevalence of lameness and attitudes on outcomes from inspections were investigated using a self-administered questionnaire. A total of 43/102 convenience–selected English sheep farmers responded to the questionnaire. Their median flock size was 500 ewes with a geometric mean prevalence of lameness of 2.8%. Few farmers selected correct descriptions of the legislation for treatment and transport of lame sheep. Participants considered 5–7.5% prevalence of lameness acceptable and were least tolerant of farmers who rarely treated lameness and most tolerant of farmers experiencing an incident out of their control, e.g. disease outbreak. Participants consider sanctions and rewards would help to control lameness on sheep farms in England. Sanctions (prosecution, reduction in payment from the single (basic) payment scheme or suspension from a farm assurance scheme) were considered “fair” when lameness was ≥10% and rewards “fair” when lameness was ≤2%. If these farmers’ attitudes are applied to 1,300 randomly selected flocks with a mean prevalence of lameness of 3.5%, 24.6% flocks had ≥10% lameness and would be sanctioned and 32.5% flocks had ≤2% lameness and would be rewarded.